PELATIHAN PEMBUATAN NUGGET N-MUSROOM SEBAGAI ALTERNATIF MAKANAN SEHAT IBU-IBU PKK DESA PATALAGAN KABUPATEN KUNINGAN - Efriani, Like; Putra, Teguh Adiyas; Gunawan, Ucha Indra (Nindikayla Institute, 2023)
Patalagan Village has various types of plants that are diverse and efficacious and can be used as home preparations that can be utilized as a source of food production and so on and can also be marketed to various regions. One of the superior potentials that can be utilized by the community as a source of income is oyster mushrooms. The purpose of this community service is to increase the knowledge of Patalagan Village residents regarding the benefits of oyster mushrooms and improve the skills of housewives in making nuggets from oyster mushrooms. The materials used are oyster mushrooms, while the methods used are socialization and counseling as well as training in making N-mushroom nuggets and product making demonstrations carried out by PKK women in Patalagan Village. The result of this training was that the participants became trained in making N-mushroom nuggets. This can be seen from the products produced by participants with good results in terms of appearance. The conclusion is that there is an increase in villagers' knowledge of the benefits of oyster mushrooms as can be seen from the results of the pretest and posttest activities given to participants where there is an increase in scores before and after the counseling and the PKK women of Patalagan Village are skilled in making